Exploring the genetic architecture of protein secretion in Komagataella phaffii (Pichia pastoris) for biotechnology applications. - Chantle Reiko Swichkow; Joshua S Bloom; Leonid Kruglyak (PLoS Biology, 2022)
Improvements to the production of proteins in industrial yeast species have largely relied on generating variation in a single genetic background. A new study in PLOS Biology leverages natural genetic variation to identify genes and variants with the potential to improve protein yield.